An urban-rural and sex differences in cancer incidence and mortality and the relationship with PM2.5 exposure: An ecological study in the southeastern side of Hu line. (February 2019) - Wang, Hong; Gao, Zhiqiu; Ren, Jingzheng; Liu, Yibo; Chang, Lisa Tzu-Chi; Cheung, Kevin; Feng, Yun; Li, Yubin
Abstract: This study investigates the urban-rural and sex differences in the increased risks of the ten most common cancers in China related to high PM2.5 concentration in the southeastern side of Hu line. Pearson correlation coefficient is estimated to reveal how the cancers closely associated with PM2.5 long-term exposure. Then linear regression is conducted to evaluate sex- and area-specific increased risks of those cancers from high level PM2.5 long-term exposure. The major finding is with the increase of every 10 μg/m 3 of annual mean PM2.5 concentration, the increase of relative risks for lung cancer incidence and mortality are 15% and 23% for males, and 22% and 24% for females in rural area. For urban area, the increase of relative risk for ovarian cancer incidence is 9% for females, while that for prostatic cancer increases 17% for males. For leukemia, the increase of relative risks for incidence and mortality are 22% and 19% for females in rural area, while in urban area the increase of relative risk for mortality is 9% for males and for incidence is 6% for females. It is also found that with increased PM2.5 exposure, the risks for ovarian and prostatic cancer rise significantly in urban area, while risks for lung cancer and leukemia rise significantly in rural area. The results demonstrate the higher risks for lung cancer and leukemia with increased PM2.5 exposure are more significant for female. This study also suggests that the carcinogenic effects of PM2.5 have obvious sex and urban-rural differences. Highlights: Increased risks for lung, ovarian, prostate cancers and leukemia are closely associated with increased PM2.5 exposure (Short version: Lung/ovarian/prostate cancer and leukemia are closely related with increased PM2.5 ). PM2.5 significantly impacts the risks for lung cancer and leukemia in rural area. PM2.5 significantly impacts the risks for prostate and ovarian cancers in urban area. Females are at higher risks for lung cancer and leukemia due to elevated PM2.5